2010
DOI: 10.1179/136217110x12785889550064
|View full text |Cite
|
Sign up to set email alerts
|

Advances in friction welding process: A review

Abstract: Friction welding is now well established as one of the most economical and highly productive methods in joining similar and dissimilar metals. It is widely used in automotive and aerospace industrial applications. Friction welding is often the only viable alternative in this field to overcome the difficulties encountered in joining the materials with widely varying physical characteristics. This process employs a machine that is designed to convert mechanical energy into heat at the joint to weld using relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
123
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(140 citation statements)
references
References 94 publications
(159 reference statements)
0
123
0
2
Order By: Relevance
“…Though FSW basics have been previously described in a few review papers, e.g. [1][2][3][4][5], some issues regarding the process-microstructure-properties relationship remain unclear and require further research. Even though it has been already found that high-quality, sound welds with good mechanical properties may be produced between non-weldable aluminum alloys of the 7000 series [6,7], the phenomena occurring spontaneously after welding (natural aging) in these alloys need further explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Though FSW basics have been previously described in a few review papers, e.g. [1][2][3][4][5], some issues regarding the process-microstructure-properties relationship remain unclear and require further research. Even though it has been already found that high-quality, sound welds with good mechanical properties may be produced between non-weldable aluminum alloys of the 7000 series [6,7], the phenomena occurring spontaneously after welding (natural aging) in these alloys need further explanation.…”
Section: Introductionmentioning
confidence: 99%
“…LFW works by oscillating one workpiece relative to another while under a compressive force [9][10][11][12]. Although a continuous process, Vairis and Frost [10] noticed that LFW occurs over four unique phases:…”
Section: Introductionmentioning
confidence: 99%
“…This causes the HAZ to have non-uniform thicknesses and also the possibility for IMC when welding dissimilar metals. These shortcomings are addressed by orbital welding [254] though very limited research work has been published on this. An inherent advantage of friction welding is significantly lower operating temperatures.…”
Section: Friction Weldingmentioning
confidence: 99%
“…Uday et al [254] completed a well-documented review of the types and mechanisms of friction welding and resulting microstructure and properties of both similar and dissimilar material joints. Three important process parameters have been shown to impact bonding: speed, pressure, and time [121,132,254].…”
Section: Friction Weldingmentioning
confidence: 99%
See 1 more Smart Citation